2019
DOI: 10.1088/1361-6463/aaf8e9
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence spectral analysis of phonon-assisted DAP and e-A recombination in N+B-dopedn-type 4H-SiC epilayers

Abstract: It is crucial to clarify the roles of phonon-assisted donor-acceptor pairs (DAPs) and free-toacceptor (e-A) emissions in n-type 4H-SiC doped with nitrogen (N) and boron (B), where N and B induce the shallow donor and the D center (deep B) acceptor levels, respectively, in order to understand the complicated carrier recombination mechanism, as well as developing fluorescent SiC with a high color rendering index by controlling the ratio of the two overlapped emissions. Here, time-resolved photoluminescence (TRPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In CL experiment two different peaks are identified in two different regions of the test sample. Therefore, these regions are related to defect states of SiC crystal and identified as region-1 is 4H-SiC polytype and region-2 is 6H-SiC polytype, respectively [26][27][28]. It is also confirmed by XRD and Raman scattering tools and to be discussed later.…”
Section: Fesem/clmentioning
confidence: 69%
See 2 more Smart Citations
“…In CL experiment two different peaks are identified in two different regions of the test sample. Therefore, these regions are related to defect states of SiC crystal and identified as region-1 is 4H-SiC polytype and region-2 is 6H-SiC polytype, respectively [26][27][28]. It is also confirmed by XRD and Raman scattering tools and to be discussed later.…”
Section: Fesem/clmentioning
confidence: 69%
“…Ou et al also observed shallow donor to deep acceptor-pair transition in SiC crystal (nitrogen to boron) around ~ 580-590 nm in 6H-SiC [26]. Liu et al and further Yang et al also identified Donor acceptor-pair emission (nitrogen to boron) for 4H-SiC crystal around 500-525 nm [27,28]. In CL experiment two different peaks are identified in two different regions of the test sample.…”
Section: Fesem/clmentioning
confidence: 93%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36] In fact, techniques to prevent the bipolar degradation were developed by locally controlling a minority carrier lifetime in an epilayer. [37][38][39] However, there exist few fundamental studies which quantitatively explain the mechanisms of the degradation in the electrical conduction due to the stacking faults (SFs), though the problem may be qualitatively discussed based on a quantum well model, i.e. the SF acts as a quantum well in the conduction band and trapped immobile electrons in the quantum well create a potential barrier for conduction electrons, resulting in the disturbance of electron transport.…”
Section: Introductionmentioning
confidence: 99%